Spontaneous rupture of renal angiomyolipoma in pregnancy mimicking preterm labour - Basri, Nurul I.; Dasrilsyah, Rima A. (BMJ Publishing Group, 2024)
Ruptured renal angiomyolipoma in pregnancy is uncommon. Pregnant women may present with nonspecific symptoms such as flank or abdominal pain, contraction pain and haematuria. A thorough assessment is needed to reach the correct diagnosis. Management varies between conservative measures, radiological intervention or surgery depending on the patient’s haemodynamic status and foetal condition. We present a case of a woman in her 30s, gravida 5 para 3+1 at 28 weeks of gestation, who presented with pain. The pain worsened, and she went into hypovolaemic shock. An exploratory laparotomy and emergency caesarean section were done. Retroperitoneal haematoma was found intraoperatively, but the source of bleeding was difficult to determine. An abdominal CT angiogram subsequently revealed an ongoing bleeding from a ruptured angiomyolipoma. An emergency nephrectomy was performed, and the bleeding was secured.